The effect of metalation processes on polymer morphology and conductivity properties. Issue 9 (November 2021) - Sarıbıyık, Oğuz Yunus; Gönül, İlyas; Ay, Burak; Karaca, Serkan
In this work, an insoluble three dimensional (3D) porous polymeric structure and their metal complexes were synthesised by the condensation reactions of meta(m) -phenylenediamine, para(p) -phenylenediamine and glutaraldehyde. The morphological and spectral features of the porous polymeric structures were determined using different analytical and spectroscopic methods, including field emission scanning electron microscopy, four-point probe electrical conductivity, photoluminescence spectroscopy, Fourier-transform infrared spectroscopy, surface area Brunauer–Emmett–Teller and magnetic and thermal behaviours. According to the obtained data, the shape, size and photoluminescence properties of the compounds, especially the conductivity, were clearly changed after the metalation processes.